2015
DOI: 10.1016/j.crohns.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-based, self-reporting symptom diary for Crohn's Disease, and its correlation with the Crohn's Disease Activity Index

Abstract: This study demonstrates that CDSD correlated well with CDAI. CDSD score of 5 is the cut-off value for clinical remission (CDAI score ≤150). Use of CDSD might permit a simple, patient-friendly assessment of CD activity, which can provide useful early-phase information on patients with CD as part of their long-term clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…However, decision support tools in IBD are now feasible as current eHealth technologies can provide the necessary components, including functionalities that allow recording of PRO and clinical biomarkers, validated disease severity indices on which algorithms can be based and a means of automatically delivering treatment suggestions in real time . Validated disease activity indices, such as the Crohn Disease Activity Index (CDAI) and the Simple Clinical Colitis Activity Index (SSCAI), can be reliably completed by patients using eHealth tools to measure disease activity . Moreover, home‐based measurement of faecal calprotectin is feasible and has been shown to agree with hospital‐based enzyme‐linked immunosorbent assays (ELISA) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decision support tools in IBD are now feasible as current eHealth technologies can provide the necessary components, including functionalities that allow recording of PRO and clinical biomarkers, validated disease severity indices on which algorithms can be based and a means of automatically delivering treatment suggestions in real time . Validated disease activity indices, such as the Crohn Disease Activity Index (CDAI) and the Simple Clinical Colitis Activity Index (SSCAI), can be reliably completed by patients using eHealth tools to measure disease activity . Moreover, home‐based measurement of faecal calprotectin is feasible and has been shown to agree with hospital‐based enzyme‐linked immunosorbent assays (ELISA) …”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Validated disease activity indices, such as the Crohn Disease Activity Index (CDAI) and the Simple Clinical Colitis Activity Index (SSCAI), can be reliably completed by patients using eHealth tools to measure disease activity. [35][36][37] Moreover, home-based measurement of faecal calprotectin is feasible and has been shown to agree with hospital-based enzyme-linked immunosorbent assays (ELISA). 38,39 Previous eHealth decision support tools have lacked a multi-stage design process with appropriate consultation, which is necessary given the complex interactions between key stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…26 While the evidence supporting the utility of telemedicine and internet-based interventions in IBD is emerging, the evidence supporting the efficacy of mobile phone apps in the CD setting is scarce. 20,22 Although it was not a mobile app, Kim et al, 27 found that web-based diaries using the HBI can be useful in the monitoring of clinical disease activity in patients with CD, with good correlation between HBI completed through the web by the patient and the CDAI calculated by the medical staff. Recently, Van Deen et al 9 developed and validated a scoring system to monitor disease activity in patients with CD and UC that can be used with mobile technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The features of the CDSD have been described in detail in a previous study [ 8 ]. Briefly, it was composed of five clinical parameters based on the Harvey-Bradshaw index: general well-being, abdominal pain, number of liquid stools per day, abdominal mass, and presence of CD-associated complications.…”
Section: Methodsmentioning
confidence: 99%
“…We recently developed a web-based self-reporting Crohn’s Disease Symptom Diary (CDSD) using the http://www.cdsd.or.kr website and reported that it corresponded well to the CDAI, with a CDSD score of 5 as the cut-off value of clinical remission [ 8 ]. Patients can record their symptoms at any moment through a smartphone.…”
Section: Introductionmentioning
confidence: 99%